Emotion Perception in Members of Norwegian Mensa - Egeland, Jens (Frontiers in Psychology, 2019)
Are people with superior intelligence also superior in interpreting the emotions of others? Some studies find that an underlying g-factor links all mental processes leading to an expectation of a positive answer to the question, while other studies find that there is a cost to giftedness. No previous study have tested social cognition among highly gifted, or the Mensa society specifically. The study measures emotion recognition in 63 members of the Norwegian Mensa and 100 community controls. The Mensa group had a higher total score on the EmoBio test and was specifically better at differentiating the anger emotion, otherwise hypthesized to be mediated by subcortical processes. There was no difference in heterogeneity between the groups, contrary to the expectation of an autistic subgroup in Mensa. The study indicate that the positive manifold extends also to social cognition, and runs counter to the concept of a cost to giftedness.